Discussion on the Social Rate of Discount: from Sen to Behavioural Economics - Adam Karbowski (Economics and Sociology, 2016)
This survey paper discusses the links between (1) research done by Amartya K. Sen on the social rate of discount and (2) behavioural economics studies on intertemporal and interpersonal choice. Sen's idea on the need to differentiate social rate of discount allowed to pave the way further followed by behavioural economists who do research on both (i) time (also known as delay or temporal) discounting and (ii) social discounting. Canonical works of Sen, Marglin, Tullock and Baumol on social rate of discount and newer (even recent) behavioural economics literature on choices made within time and social distance horizon strongly complement each other. As shown, the works of Sen considerably broadened the standard approach (discounted utility model) to the intergenerational choice as well as significantly affected economic debate in that area for years to come. Brief presentation of the discounted utility model and its implications is a first research task of this paper. The concise elaboration of research findings of (a) Sen and (b) behavioural economists comprises two remaining research tasks of this paper.
Keywords: D6; D9; 330; behavioral economics; social rate of discount